If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -1x = -8 Solving -3 + -1x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = -8 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -8 + 3 -1x = -8 + 3 Combine like terms: -8 + 3 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| Sin^2x+20sinx+91=0 | | 3/4x+5/x=1 | | 13=4(x-4)-(x-8) | | 28x^3-21x^2-7x=0 | | 18=-3x-4 | | 20x+30+5x+40=570 | | 20x+30+5x+40=574 | | -7-3x=-12 | | 10cos^2x-11cosx-6=0 | | 20x+30+5x+40=576 | | 20x+30+5x+40=581 | | 20x+30+5x+40=582 | | -3=-4-11x | | 20x+30+5x+40=579 | | -6x-1=-14 | | 20x+30+5x+40=580 | | d+32=108 | | 5y-9=13y+7 | | 20x+30+5x+40=600 | | -24x^3-8x^2=0 | | 20x+30+5x+40=700 | | 7=5-3x | | 4/9=x/15 | | 5m=250 | | 20x+30+5x+40=220 | | 12y+35=3 | | 5-2x=-4 | | 3x^2-17x+12=y | | 3/2X+1/2X | | 3x-8x+7=3x-8+11x | | 11=-8x+4 | | 6x-(4x-3)=11 |